Rice Straw Craft Preservation and Development in Nagano Prefecture, Japan - Pandu Purwandaru (Mudra Jurnal Seni Budaya, 2023)
The Japanese rice straw culture began in the Yayoi period approximately 2000 years ago. This culture can be found in almost all areas of Japan, including the Nagano Prefecture. One of the supporting elements of the rice straw culture development in this area is because it has been recognized as a potential rice farming area. Based on the historical evidence displayed in a number of museums, there are various traditional uses of rice straw for utility, ritual, and celebration needs. Unfortunately, the number of workshops and craftsmen is currently decreasing due to modernization. However, there are still several workshops that still exist and are actively producing rice straw crafts. Therefore, this research was conducted to understand various supporting aspects in the preservation and development program of rice straw crafts in Nagano Prefecture. From the mapping results in Otarimura and Azumino, it may be concluded that the character of the rice straw crafts produced those areas is through coiling and basket weaving methods. There are five elements that support the development of these crafts, namely human resources, production methods, design development, support from the government and private sector, and the market.